The Sealtest Building, New York World's Fair 1939 (Grinnell Litho Co.)
This unusual building houses exhibits dramatizing the research and quality control supervision of Sealtest System of Laboratory Protection. Demonstration units showing the manufacture of various products are included among its many exhibits.